Encounters with haunted industrial workplaces and emotions of loss: class-related senses of place within the memories of metalworkers. (October 2013) - Meier, Lars
This article is about the relevance of social class within emotional geography. Based on life history interviews with former metalworkers in Bavaria, it analyses their identity-related sense of place and the feelings of loss they experience when encountering their former places of work. By concentrating on the perspective of those who have worked on industrial sites, and their encounters with those sites, now transformed, this article focuses on a specific identity-related emotion experienced by working-class people, which is often underestimated. Recollections of common experiences linked to the workplace may seem haunting in the form of memories of body routines within a place ballet, or of former buildings and walls. Workers describe how, when they visit their former workplace, they have to confront this haunting from the past; and it is through these haunting experiences that their class identity takes on a new but often painful existence.